Trend in incidence of gastric adenocarcinoma by tumor location from 1969-2004: a study in one referral center in Iran - Nadimi-Barfroosh Hosein; Ghaderi-sohi Siavash; Abdi-Rad Afshin; Emami Sara (BMC, 2006)
Abstract Aim In recent years several studies have shown increasing rate of upper gastric cancers regarding to decrease in distal gastric cancers. The aim of this study was to describe the trend of gastric cancers by location in Iran, which is one of the countries with high prevalence of gastric cancers. Methods All registered cases of gasterectomy in Tehran Cancer Institute from 1969 through 2004 were re-evaluated clinicopathologically. The stomach was anatomically divided into the upper, middle, and lower third. The prevalence of gastric cancers in 5 year periods estimated by location and the changes trough the time was evaluated independently and in aspect of age and sex. Results Over 36 years, the prevalence of cancers in the upper and middle third of the stomach have increased and that of the lower third has decreased. These changes were seen in both sexes and age groups under and over 50 and it was more significant in younger. Conclusion The results are the same as most previous reports in other countries. This can indicate different risk factors as well as confrontation with them. However in regard to few numbers of cases in this study, a population-based study is recommended for confirmation.